Struggling for Smoke-Free Zones in Schools Against Kretek Culture - Amini, Azimatul; Kasih, Bintang; Saputri, Iga Ayu; Leily Sylraini, Mahfira (BKM Public Health and Community Medicine, 2024)
Purpose: Tobacco smoke contains thousands of harmful chemicals that can disrupt lung development in children and increase the risk of diseases such as cancer, heart disease, and stroke. Implementing Smoke-Free Zones (SFZ) in schools is crucial to protect the health of the entire school community, especially students who are still growing. Kudus City, known for its kretek culture, had 166 tobacco companies in 2024. The issuance of Kudus Regent Regulation No. 18 of 2015 concerning SFZ and Limited Smoking Areas (LSA) in Kudus, which includes school environments, provides an opportunity to implement SFZ in schools. This study discusses the importance of SFZ implementation in schools, particularly in Kudus. Methods: Data from the 2019 Global Youth Tobacco Survey (GYTS) indicated that one in five teenagers aged 15-19 smoke. The 2023 Indonesian Health Survey (SKI) showed that 18.4% of smokers first smoked at the age of 10-14 years. This data underscores the need for health promotion strategies to reduce teenage smoking rates in Indonesia. According to the Centers for Disease Control and Prevention (CDC) guidelines, smoke-free schools can protect students, teachers, and staff from the dangers of tobacco smoke, creating a healthier and more conducive learning environment. Results: Studies have shown a significant relationship between the presence of SFZ policies in schools and smoking behavior. Adolescents in schools with SFZ policies are 3.2 times more likely to have a positive attitude towards non-smoking and 2.6 times more likely to quit smoking compared to those in schools without SFZ policies. The challenge of implementing SFZ in Kudus lies in potential opposition from the tobacco industry, farmers, workers, and other stakeholders, which may impact their economic sector. Conclusion: Despite potential opposition, there is still a potential for advocacy support for implementing SFZ policies in schools to protect student health.